Synthesis, Characterization, Thermal Studies, and Molecular Structure of New Metal Complexes of Dehydroacetic Acid Hydrazone - Kashar, Tahani I.; El-Sehli, Amal H. (European Scientific Journal, ESJ, 2016)
Metal complexes of dehydroacetic acid hydrazone are synthesized and characterized by physical, chemical, and spectral studies. The ligand behaves as monobasic tetradentate coordinated with the metal ions through C=O, deprotonated phenolic oxygen, and azomethin nitrogen. The characterization data suggests a square planar geometry for Cu(II) complex and an octahedral geometry for all other complexes. The crystal and molecular structure of the [Cu(HL)]Cl.H2O complex has been established by a single crystal maXus. The thermal studies of the complexes showed that the decomposition takes place through four steps.